Perjuangan Hegemoni Global: Persaingan Amerika Serikat dan China dalam Tatanan Dunia Multipolar - Kawulur, Alvian Bagas (Maliki Interdisciplinary Journal, 2025)
The geopolitical competition between the United States and China has transformed the contemporary multipolar world order, creating significant challenges for developing countries. The research problem focuses on how the dynamics of US-China hegemonic competition affect the global balance of power and its implications for Indonesia’s strategic position. This study employs a comparative analysis approach and case studies based on structural realism theory and the concept of soft power to map the strategies of both superpowers in expanding their influence. The analysis results show that US-China competition manifests in three main dimensions: (1) economic contestation through the Belt and Road Initiative (China) versus the Indo-Pacific Economic Framework (US); (2) military rivalry particularly in the South China Sea and around Taiwan; and (3) technological competition to dominate strategic sectors such as semiconductors and artificial intelligence. Findings indicate that developing countries including Indonesia face a dilemma between leveraging economic opportunities from both powers and maintaining strategic autonomy. This research proposes solutions including strengthening collective bargaining positions through regional institutions, diversifying international partnerships, and developing national technological capabilities to maximize benefits from this hegemonic competition. In conclusion, Indonesia needs to implement proactive diplomacy that avoids polarization while building national resilience in facing increasing geopolitical pressures.